Migration of foreign labourers into Malaysia - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2013)
The influx of migrant workers into the Malay Peninsula during the British administration of the Straits Settlements and the Malay States forms the basis of this chapter. Reference is made to the introduction of the labour legislation to accord protection of these workers against exploitation and abuse by the employers. It is noteworthy that the inflow of international migrants into the Malay Peninsula is not a recent phenomenon. It started during the British colonial rule when the capitalist economic enterprises were introduced together with necessary infrastructures. Apart from the above, it is also worthwhile to briefly note the abolishment of serfdom and slavery in England. The above discussion is relevant in so far as the treatment of migrant workers during the British administration of the Straits Settlements and the Malay States is concerned.